2021
DOI: 10.5152/anatoljcardiol.2021.89304
|View full text |Cite
|
Sign up to set email alerts
|

Time for a new paradigm shift in myocardial infarction

Abstract: The ST-elevation myocardial infarction (STEMI)/non-STEMI paradigm per the current guidelines has important limitations. It misses a substantial proportion of acute coronary occlusions (ACO) and results in a significant amount of unnecessary catheterization laboratory activations. It is not widely appreciated how poor is the evidence base for the STEMI criteria; the recommended STEMI cutoffs were not derived by comparing those with ACO with those without and not specifically designed for distinguishing patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Recently, Aslanger et al 4 have published a review where they state that, beyond STEMI, there are certain clinical characteristics in patients with NSTE-ACS that require and benefit from an immediate reperfusion strategy which is in accordance with other authors. 5 …”
supporting
confidence: 56%
“…Recently, Aslanger et al 4 have published a review where they state that, beyond STEMI, there are certain clinical characteristics in patients with NSTE-ACS that require and benefit from an immediate reperfusion strategy which is in accordance with other authors. 5 …”
supporting
confidence: 56%
“…STEMI criteria alone may not be sufficient to rule in all acute coronary artery occlusions. Aslanger et al reported that we needed to recognize subtle ECG changes in treating in the patients with acute coronary syndrome [6][7][8][9]. Therefore, Pendell Meyers et al reported that other diagnostic tools need to be determined to compensate for STEMI criteria [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pooled data from these trials were studied in the seminal fibrinolytic therapy trialists’ meta-analysis,[ 6 ] which showed an impressive reduction in mortality with a slightly better benefit in patients with (ambiguously and inconsistently defined) STE compared to general cohort. [ 1 ] This was an unparalleled revolution in cardiology which made “reperfusion medicine” the norm.…”
Section: What Is a St-segment Elevation Myocardial Infarction?mentioning
confidence: 99%
“…[ 13 14 15 16 17 18 19 20 21 ] This suggests that, when STEMI criteria are not met, the physicians do not manage to identify the patients with ACO among all patients with undifferentiated persistent chest pain partly because it may be present in many other competing diagnoses. [ 1 2 ] Furthermore, STEMI criteria were shown to have only a prospective sensitivity of 21% and 49% for ACO when a computer algorithm and cardiologist evaluation were used, respectively. [ 22 ] Physicians across different specialties have poor accuracy and poor interrater reliability for detecting ACO[ 23 ] and cannot even agree on where and how to measure the STE.…”
Section: Can a Non-st-segment Elevation Myocardial Infarction Still B...mentioning
confidence: 99%
See 1 more Smart Citation